Mencandra To Manurung sebagai Peletak Dasar Budaya Politik Sulawesi Tenggara dan Sulawesi Selatan - Rifai Nur (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
This journal article is lifted from the writer’s dissertation entitled “Regional Autonomy and Obstacles in Their Implementation in The South and Southeast Sulawesi, 1950-1959”. One of the chapters in the dissertation was about the political culture. That chapter was adapted in this paper with the title; Mencandra To Manurung as a foundress of political culture in Southeast Sulawesi and South Sulawesi. The issue in this article is why To Manurung as Foundress of society Cultural politics of Southeast Sulawesi and South Sulawesi. The goal is to analyze why To Manurung became the Foundress political culture Community in Southeast Sulawesi and South Sulawesi. The research method used is descriptive qualitatif strukturis type. Data collection through the study of documentation and interviews. The analysis of the data used are: (1) reduction of data, data presentation (10, (3) a false assertion and perivikasi data. The research result are: (1) political Ethics ' Sulapa Eppa ' who bequeathed the character and style of leadership: honest, defender of truth, justice enforcement, courageous in upholding truth, justice and the well-being of society at large; (2) major blood ' Takku ' white blood makes a person appear as giver of goodness, peace, harmony and prosperity with high integrity who bequeathed the behavior of giving without taking. It means taking something as a konsekuaensi term, instead of the jabatnnya exploit to get something from the State and society. Keywords: To Manurung, politic culture, social structure